Piezoelectric vibrator and its manufacturing method

By using ultrasonic probes made of single crystals of magnesium oxygen, yttrium oxygen and lead lithium titanate, alternating electroporation and heat treatment methods, the problem of insufficient electrical performance of dielectric loss in the prior art is solved, and the effects of high sensitivity and low heat generation are achieved.

JP7667664B2Active Publication Date: 2025-04-23唐木 智明 +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021031600
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-01
Publication Date
2025-04-23
Estimated Expiration
2041-03-01

AI Technical Summary

Technical Problem

In the prior art, the dielectric loss of high-performance ultrasonic probes is large, resulting in heat generation, and the relative dielectric constant and voltage constant d33 are insufficient, making it difficult to meet the needs of high sensitivity and low heat generation.

Method used

A rectangular single crystal panel made of magnesium oxygen, yttrium oxygen and lead lithium titanate single crystals is used to optimize its structure and electrical properties by forming electrodes on both sides of it.

Benefits of technology

It effectively reduces unnecessary vibration, reduces dielectric loss, improves dielectric constant, coupling coefficient k33 and voltage constant d33, and realizes a high sensitivity and low heat generation ultrasonic probe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667664000003
    Figure 0007667664000003
  • Figure 0007667664000004
    Figure 0007667664000004
  • Figure 0007667664000005
    Figure 0007667664000005
Patent Text Reader

Abstract

To provide a piezoelectric vibrator having higher dielectric characteristics and piezoelectric characteristics and also having good manufacturing yield, and a manufacturing method thereof.SOLUTION: A piezoelectric vibrator includes a rectangular single crystal plate 1 comprising a lead composite perovskite compound containing magnesium oxide and niobium oxide, and lead titanate. The single crystal plate 1 is characterized in that a ratio L / W of a length L in the [100] orientation and a width W in the [010] orientation is 3-10, and a ratio Nt / N31 of a frequency constant N31 that is represented by a product of a resonance frequency fr in a lateral vibration mode orthogonal to a polarization direction and the length L of the single crystal plate 1, and a frequency constant Nt that is represented by a product of a resonance frequency fr in a longitudinal vibration mode parallel to the polarization direction and a thickness t of the single crystal plate 1, is 2.75 to 3.9 at 25°C. The piezoelectric vibrator 1 is manufactured by, after performing AC polarization at first, performing heat treatment, and AC polarization and depolarization at a temperature of 150°C or above and 300°C or below, and, after repeating this process at least twice to 4 times, performing last AC polarization of the single crystal plate 1.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a piezoelectric transducer used in an ultrasonic probe of an ultrasonic image inspection device such as a medical ultrasonic diagnostic device, a fish finder, or a sonar, and a method for manufacturing the same. [Background technology]

[0002] Ultrasonic imaging devices such as medical ultrasonic diagnostic devices, fish finders, and sonars irradiate ultrasonic waves to an object via an ultrasonic probe, and image the inside of the object based on the reflected signals (echo signals) generated by the waves reflected from inside the object. Medical ultrasonic diagnostic devices and ultrasonic imaging devices mainly use electronically scanned array-type ultrasonic probes with ultrasonic transmission and reception functions, and high-performance piezoelectric transducers are used for this purpose.

[0003] A typical ultrasonic probe has a backing material, a piezoelectric transducer bonded onto the backing material with electrodes formed on both sides of the piezoelectric body, and an acoustic matching layer bonded onto the piezoelectric transducer. The piezoelectric transducer and the acoustic matching layer are formed into multiple channels by array processing. An acoustic lens is formed on the acoustic matching layer. The electrodes of the piezoelectric transducer corresponding to each channel are connected to the main body of the medical ultrasonic diagnostic device or ultrasonic imaging device via a control signal board (flexible printed circuit, FPC) and a cable.

[0004] The piezoelectric transducers used here are generally DC polarized. DC polarization is performed by forming electrodes on the top and bottom surfaces of the piezoelectric ceramics or single crystal plate, and applying a DC voltage for about 1 to 30 minutes in air or silicone oil. In the array-type ultrasound probes of medical ultrasound diagnostic equipment, which are the mainstream for this application, a high dielectric constant and an electromechanical coupling coefficient k in the longitudinal direction of the rod are required to match the electrical impedance of the fine rectangular piezoelectric transducer (e.g., width 0.15 mm, height 0.3 mm, length 10 mm) to the approximately 50 Ω of the connecting cable. 33 and the piezoelectric constant d 33Therefore, a high-performance piezoelectric material with a high-temperature property is desired. 1 / 3 Nb 2 / 3 )O 3 (PMN)-Lead Titanate PbTiO 3 (PT)-based solid solution single crystals have been widely used since 2000.

[0005] Attempts are also being made to improve the polarization process to enhance the performance of piezoelectric vibrators. For example, Patent Document 1 shows that the electromechanical coupling coefficient and dielectric constant of a piezoelectric element can be improved by performing an electric field cooling polarization process on a two-component piezoelectric material based on lead zinc niobate-lead titanate while applying a DC voltage from high to low temperatures.

[0006] On the other hand, Patent Documents 2 and 3 show that the dielectric constant, coupling coefficient and piezoelectric constant of a PMN-PT piezoelectric vibrator can be improved by manufacturing the piezoelectric element through AC polarization treatment in which an AC electric field is applied instead of a DC electric field. In addition, Non-Patent Document 1 shows that high piezoelectric properties can be obtained in a low AC electric field by performing AC polarization at a high temperature of around 80°C. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 7-50898 A [Patent Document 2] JP 2014-045411 A [Patent Document 3] JP 2014-187285 A [Non-patent literature]

[0008] [Non-Patent Document 1] Yiqin Sun et al. Jpn.J. Apply. Phys. 59, SPPD08 (2020) Summary of the Invention [Problem to be solved by the invention]

[0009] However, even in the ultrasonic transducers using the piezoelectric single crystal materials disclosed in the above-mentioned conventional prior art documents, further improvement in performance is required in order to obtain ultrasonic probes with higher performance. It is necessary to reduce the dielectric loss, which is the cause of heat generation, without generating unnecessary vibrations, and to improve the relative dielectric constant and the piezoelectric constant d 33 There was a demand for a piezoelectric vibrator with improved characteristics.

[0010] The present invention has been made in view of the above-mentioned background art, and has an object to provide a piezoelectric vibrator having higher dielectric properties and piezoelectric properties and a good manufacturing yield, and a method for manufacturing the same. [Means for solving the problem]

[0011] The present invention provides a piezoelectric vibrator formed of a rectangular single crystal plate composed of a lead complex perovskite compound containing magnesium oxide, niobium oxide, and lead titanate, and having electrodes on both sides, the single crystal plate having a crystal orientation of

[0001] as a main surface, and

[0100] and

[0010] as side surfaces, a ratio L / W of the length L of the single crystal plate in the

[0100] orientation to the width W of the

[0010] orientation being 3 to 10, and a frequency constant N expressed by the product of a resonance frequency fr of a lateral vibration mode perpendicular to the polarization direction and the length L. 31 and a frequency constant N expressed by the product of the resonance frequency fr of the longitudinal vibration mode parallel to the polarization direction and the thickness t of the single crystal plate. t Ratio of N t / N 31 is 2.75 to 3.9 at 25° C. In particular, the ratio N t / N 31 is preferably 2.8 to 3.6 at 25° C., and more preferably 2.9 to 3.2.

[0012] The lead complex perovskite compound is lead magnesium niobate (100-x)Pb(Mg 1 / 3 Nb 2 / 3 )O 3, lead titanate xPbTiO 3 The piezoelectric vibrator is made of a two-component system, and contains x mol % (x is a positive value) lead titanate and (100-x) mol % lead magnesium niobate, and has a temperature Tm showing a maximum dielectric constant of 125°C to 150°C, where x is 27 or more and 32 or less. Furthermore, the phase transition temperature T rt It is preferable that the temperature is 60°C or higher and 110°C or lower.

[0013] The present invention also relates to a method for producing a piezoelectric vibrator, comprising the steps of: first, performing heat treatment, AC polarization and depolarization on the single crystal plate which has been AC polarized at a temperature of 150° C. or higher and 300° C. or lower; The method includes the steps of: This is a method for manufacturing a piezoelectric vibrator, in which the process is repeated at least two to four times, and then a final AC polarization is performed on the single crystal plate.

[0014] The AC electric field in the AC polarization is 1.0 kVrms / cm to 10 kVrms / cm (rms: Root Mean Square) and is an AC electric field having a frequency of 0.01 Hz to 200 Hz using a triangular wave or a sine wave, and is applied for 4 to 200 cycles. The temperature in the AC polarization is preferably in the range of 20°C to 90°C.

[0015] The last AC Polarization Then, a DC electric field in the range of 2.0 kV / cm to 10 kV / cm is applied between the front electrode and the back electrode of the single crystal plate for 6 seconds to 1 minute. The strength of the DC electric field is preferably 0.8 to 1.5 times the strength of the AC electric field.

[0016] Furthermore, the AC electric field is 2.0 kVrms / cm or more. 4.0 kVrms / cm or less, and the DC electric field is 3.0 kV / cm or more 5.0kV / cm The polarization temperature is preferably in the range of 40° C. to 70° C. Effect of the Invention

[0017] According to the piezoelectric vibrator and the manufacturing method thereof of the present invention, the generation of unwanted vibrations is suppressed, the dielectric loss is small, and the specific dielectric constant and the coupling coefficient k 33 and the piezoelectric constant d 33 It is therefore possible to easily and reliably manufacture a piezoelectric vibrator having the above-mentioned features, thereby making it possible to stably provide an ultrasonic device that has high resolution, high sensitivity, and generates little heat. [Brief description of the drawings]

[0018] [Figure 1] 1 is a perspective view showing an example of the appearance of a piezoelectric vibrator according to an embodiment and example of the present invention; [Diagram 2] FIG. 1A is a process diagram showing a manufacturing process of a piezoelectric vibrator according to an embodiment and example of the present invention, and FIG. 1B is a process diagram showing a manufacturing process of a conventional piezoelectric vibrator. [Diagram 3] 1 is a graph showing an example of a process for manufacturing a piezoelectric vibrator according to an embodiment and example of the present invention, in which after electrodes are formed, AC polarization is performed, and then heat treatment depolarization is performed at 150° C. or higher, and the process is repeated 2-3 times. [Figure 4] 11 is a graph showing the relationship between the frequency constant N31 in the length direction and Nt / N31 which is the ratio of the frequency constant Nt in the thickness direction to the frequency constant N31 in the length direction in a piezoelectric vibrator according to an embodiment and example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described with reference to Figures 1 to 4. First, a piezoelectric vibrator according to the present embodiment and a method for manufacturing the same will be described below.

[0020] First, lead magnesium niobate (Pb(Mg 1 / 3 Nb 2 / 3 )O 3 (hereinafter referred to as PMN), lead indium niobate (Pb(In 1 / 2 Nb 1 / 2 )O 3 (hereafter referred to as PIN), lead titanate PbTiO 3In order to produce a piezoelectric single crystal having a PT, the following raw materials are mixed in a specific ratio. 3 O 4 , MgO, Nb 2 O 5 , In 2 O 3 , TiO 2、 ZrO 2 These raw materials are weighed out in a predetermined ratio. The weighed raw materials are mixed in a wet state using a ball mill, zirconia balls, and distilled water. The mixed raw materials (hereinafter referred to as the mixed raw material) are dried for a predetermined time. The dried mixed raw material is pre-fired several times at 850 to 950°C. This pre-fire produces raw material powder of the mixed raw material. Also, some of the raw materials, particularly MgO or In, are pre-fired. 2 O 3 and Nb 2 O 5 Only MgNb with columbite structure was mixed. 2 O 6 and InNbO 4 was prepared at about 1200℃, and then another material, TiO 2 and Pb 3 O 4 etc. may be mixed.

[0021] A water-soluble binding agent (binder) such as polyvinyl alcohol (PVA) is added to the raw material powder produced in an amount of 0.5 to 10% of the raw material powder. The raw material powder to which the binder has been added is molded into a predetermined shape using a press machine. After molding, a binder removal process is carried out at 500°C for several hours. The molded body from which the binder removal process has been carried out is fired at 1100 to 1250°C for several hours. Hereinafter, the fired molded body will be referred to as a ceramic for single crystal.

[0022] The ceramics for single crystals are placed in a platinum crucible with a diameter and length of 25 to 100 mm and a diameter of 50 to 200 mm. In some cases, a small amount of lead oxide or boron oxide is added to lower the melting point of the ceramics. A single crystal seed with the same composition and crystal orientation of

[0001] plate or

[0110] plate is placed in the lower part of the platinum crucible. The length of the

[0001] plate or

[0110] plate of the single crystal seed is 20 to 70 mm. The upper part of the platinum crucible containing the ceramics and seeds is sealed by welding. The temperature of the sealed platinum crucible is kept at 1100 to 1400°C for 5 to 15 hours. This allows the ceramics in the platinum crucible to completely melt. At this time, in order not to melt the seeds placed at the bottom of the platinum crucible, a temperature gradient is provided from the bottom to the top of the platinum crucible, where the temperature rises at 20 to 60° C. / cm.

[0023] Thereafter, in order to grow a long single crystal, the platinum crucible is lowered at 0.2 to 0.6 mm / hour in accordance with the temperature gradient and the growth of the single crystal. It is also possible to produce a large and long ingot with high uniformity by adding ceramic raw material during the crystal growth. In order to increase the uniformity of the temperature and composition in the crucible during the growth, the platinum crucible is rotated at a speed of 3 to 30 times per minute. Through the above steps, the growth of the single crystal is carried out for a total of 10 to 30 days. Through the above manufacturing steps of the Bridgman method, a piezoelectric single crystal ingot with a diameter of 25 to 100 mm and a length of 50 to 150 mm is produced.

[0024] That is, the ingot of the piezoelectric single crystal to be produced is made of at least lead titanate (PbTiO 3 ) and relaxor-based lead complex perovskite compounds (Pb(B 1 , B 2 )O 3 ):(B 1 At least one of magnesium and indium, B 2In addition to the Bridgman method, the method for producing the piezoelectric single crystal ingot includes the flux method, the molten Bridgman method, the TSSG (Top Seeded Solution Groth) method, the horizontal melting Bridgman method, and the CZ (Czochralski) method. The present invention is not limited to the above-mentioned method for producing the piezoelectric single crystal ingot. It is sufficient to produce a piezoelectric single crystal by any of the above-mentioned methods.

[0025] Lead complex perovskite compounds have a rhombohedral to tetragonal phase transition temperature (T rt ) and the phase transition temperature from the rhombohedral system to the monoclinic system (hereafter referred to as T rm ) and the phase transition temperature from monoclinic to tetragonal (hereafter referred to as T mt The phase transition temperature T rt When the phase transition temperature T is less than 60°C, the dielectric constant and the coupling coefficient are high at room temperature, but the temperature dependence of these electrical properties becomes significant. rt If the phase transition temperature T exceeds 110°C, the desired relative dielectric constant and piezoelectric properties cannot be obtained at room temperature, as described below. rt The temperature range of is preferably 60° C. or more and 110° C. or less. In order to have both excellent piezoelectric properties and temperature characteristics, the phase transition temperature is more preferably 80° C. to 95° C.

[0026] Specifically, the lead complex perovskite compound contains 68 mol% to 73 mol% lead magnesium niobate or lead indium niobate, and 27 mol% to 32 mol% lead titanate. This is because if the ratio of lead titanate to the lead complex perovskite compound is less than 27 mol%, a high relative dielectric constant, coupling coefficient, and piezoelectric constant cannot be obtained. Also, if the ratio of lead titanate to the lead complex perovskite compound exceeds 32 mol%, the phase transition temperature T rmAt a temperature of 60° C. or less, the temperature dependence of the dielectric constant and coupling coefficient becomes significant, particularly at room temperature to 50° C. Therefore, in order to maintain a high dielectric constant, coupling coefficient, and piezoelectric constant, and to reduce the above-mentioned temperature dependence at room temperature to 50° C., the ratio of lead titanate in the lead complex perovskite compound must be 27 mol % or more and 32 mol % or less, and more preferably 29 mol % or more and 31 mol % or less.

[0027] From the above, the piezoelectric single crystal produced in this embodiment has a phase transition temperature T rt The temperature is 60°C or higher and 110°C or lower, and the lead complex perovskite compound is lead magnesium niobate (100-x)Pb(Mg 1 / 3 Nb 2 / 3 )O 3 , lead titanate xPbTiO 3 It is a two-component piezoelectric material. Here, it contains x mol% (x is a positive value) lead titanate and (100-x) mol% lead magnesium niobate. The temperature Tm at which the relative dielectric constant is maximum is 125°C to 150°C, and x is 27 or more and 32 or less.

[0028] The lead complex perovskite compound may further contain lead indium niobate and lead zirconate. If the ratio of lead indium niobate to the lead complex perovskite compound exceeds 30 mol%, it becomes difficult to prepare a single crystal of the lead complex perovskite compound, and a single crystal of the lead complex perovskite compound composed of three components (lead indium niobate, lead magnesium niobate, lead titanate) having high uniformity may not be obtained.

[0029] Furthermore, in order to maintain a high relative dielectric constant and coupling coefficient and reduce the above-mentioned temperature-dependent characteristics at room temperature to 50° C., the lead complex perovskite compound may contain 0 mol % to 30 mol % lead indium niobate, 36 mol % to 68 mol % lead magnesium niobate, and 27 mol % to 32 mol % lead titanate, the total of which may be 100 mol %. The piezoelectric single crystal of this embodiment may further contain 15 mol % or less of lead zirconate.

[0030] Here, the crystal orientation of the piezoelectric vibrator used in the ultrasonic probe is mainly a piezoelectric single crystal with a

[0001] orientation, which has excellent piezoelectric properties. In addition, a small amount (2.0 mol% or less) of manganese oxide or the like may be added to the piezoelectric single crystal of these piezoelectric vibrators. Here, in this embodiment and the present invention, the crystal orientation is the orientation shown by the arrow in Figure 1, and the length L, width W, and thickness t of the piezoelectric vibrator 1 also correspond to the orientation shown in Figure 1.

[0031] In order to set the driving center frequency of the ultrasonic probe to 2 MHz or more and 12 MHz or less, the piezoelectric transducer of the ultrasonic probe used in a medical ultrasonic diagnostic device and an ultrasonic image inspection device has a thickness of, for example, 0.05 mm or more and 0.5 mm or less.

[0032] From the single crystal ingot obtained by the above method, a diamond blade or wire saw having a thickness of 0.1 to 0.5 mm is used to produce multiple wafers (hereinafter referred to as single crystal wafers) having a thickness of 0.2 to 0.7 mm from near the center of the single crystal ingot. As shown in Figure 1, the thickness direction of the single crystal wafer is the crystal orientation

[0001] , the length direction L is

[0100] , and the width direction W is

[0010] . Next, by lapping or polishing, a single crystal plate having a thickness of, for example, 0.05 mm to 0.5 mm and a crystal orientation of

[0001] on the surface on which the electrode is to be produced is produced.

[0033] Then, electrodes are formed on the surface of the single crystal plate. The electrodes are made of baked silver or gold, or gold, platinum, or nickel prepared by sputtering or plating, and are formed on the front and back of the single crystal plate with a thickness of about 100 nm to 5000 nm. Hereinafter, the electrode provided on the front of the single crystal plate is called the front electrode, and the electrode provided on the back of the single crystal plate is called the back electrode. When attaching electrodes by sputtering, vapor deposition, or plating, it is desirable to provide chromium (Cr), nickel (Ni), titanium (Ti), palladium (Pd), or the like as a base electrode with a thickness of about 10 nm to 100 nm in order to improve adhesion with the single crystal plate. Hereinafter, the single crystal plate provided with electrodes is called a piezoelectric single crystal vibrator.

[0034] The unpolarized piezoelectric single crystal vibrator is subjected to the next AC polarization process. The polarization electric field in the AC polarization process is an AC electric field of a sine wave or triangular wave with a frequency of 0.01 Hz to 200 Hz without offset (the absolute value of the maximum voltage is equal to the absolute value of the minimum voltage). A frequency of less than 0.01 Hz can provide the effect of the characteristic of the present application described later, but is not preferable because it increases the working time. Furthermore, a frequency exceeding 200 Hz is likely to cause fine cracks and insulation breakdown due to heat generation in the piezoelectric single crystal vibrator. As a result, the piezoelectric single crystal vibrator becomes more fragile and the manufacturing yield decreases.

[0035] From the above, the frequency of the AC electric field needs to be in the range of 0.01 Hz to 200 Hz. The electric field in this AC electric field is expressed by the root-mean-square (rms), which is the most commonly used value of the AC electric field. The electric field of the AC polarization required here is 1 to 5 times the coercive electric field Ec of the piezoelectric vibrator at the temperature. In an AC electric field equivalent to the coercive electric field, the increase rate of the relative dielectric constant and the piezoelectric constant in the AC polarization is 10% or less compared to the DC polarization. In addition, in an AC electric field exceeding 5 times the coercive electric field Ec, the piezoelectric single crystal vibrator is likely to generate unnecessary vibrations, generate fine cracks, and cause insulation breakdown due to heat generation and deformation. As a result, the piezoelectric single crystal vibrator becomes more likely to break. From the above, the electric field of the AC polarization needs to be in the range of 1 to 5 times the coercive electric field.

[0036] Specifically, the AC electric field is 1.0 kVrms / cm or more and 10 kVrms / cm or less. If the AC electric field is less than 1.0 kVrms / cm, it is difficult to obtain the characteristic improvement effect of the present invention described later. Furthermore, if the AC electric field exceeds 10 kVrms / cm, heat is generated in the single crystal oscillator, and as a result, the single crystal oscillator becomes more likely to break. More preferably, the AC electric field is in the range of 2.0 kVrms / cm or more and 4.0 kVrms / cm or less. One cycle of the AC electric field is defined as a process in which the AC electric field starts at 0 kVrms / cm, passes through one wavelength (one period), and ends at 0 kV / cm.

[0037] The AC polarization step is a step of applying the polarization signal in the thickness direction of the piezoelectric single crystal vibrator through the electrodes (front electrode and back electrode) for 4 to 200 cycles. If the number of cycles is less than 4, it is difficult to obtain the characteristic improvement effect of the present invention described later. Furthermore, if the number of cycles exceeds 200, heat is generated in the piezoelectric single crystal vibrator, and as a result, the piezoelectric single crystal vibrator becomes hot, especially when the electrode area is 2.0 cm2. 2 Large piezoelectric single crystal resonators exceeding this value are prone to breakage. The number of cycles and electric field mentioned above also depend on the polarization temperature. A high voltage and number of cycles are required near room temperature, while a relatively low polarization voltage and number of cycles can be used at high temperatures of around 80°C for sufficient values.

[0038] For this reason, more preferably, the polarization temperature is 40° C. to 70° C., the AC electric field is in the range of 2.0 kVrms / cm to 4.0 kVrms / cm, and the number of cycles is 10 to 50. The number of times (cycles) of application of the AC electric field may be determined depending on the composition and dimensions of the single crystal material. Note that the AC polarization step and the final DC polarization step are performed at a temperature above the phase transition temperature (T rt , T rm , T mt It is preferable that the polarization process is performed in a thermostatic chamber at a temperature (e.g., 50° C.) below the phase transition temperature, where the polarization is partially reversed and the piezoelectricity is reduced when the phase transition temperature is exceeded. In other words, the polarization process needs to be performed in a stable temperature environment below the phase transition temperature.

[0039] As shown in Figs. 2 and 3, the AC-polarized piezoelectric single crystal vibrator is heat-treated at a temperature of 150°C to 300°C, depolarized, and this process is repeated at least two to four times before the final AC polarization. Furthermore, DC polarization may be performed after the final AC polarization, and it is preferable that DC polarization is performed continuously after the final AC polarization process. This is mainly because when a vibrator is produced only by AC polarization, non-uniform polarization processing occurs in the plane, which leads to the generation of unnecessary vibration. For this reason, for example, the electric field used in DC polarization is preferably 0.8 to 1.5 times the AC polarization electric field Vrms / cm. By combining multiple AC polarizations and the final DC polarization in this way, a piezoelectric vibrator with excellent electrical characteristics can be stably produced with a high manufacturing yield. Specifically, the electric field used in DC polarization is preferably 3.0 kV / cm to 5.0 kV / cm. The time for which the DC polarization is performed is, for example, from room temperature (15 to 25° C.) to 50° C., and generally from 10 seconds to 1 minute.

[0040] In addition, the piezoelectric constant d 33 The measurement was performed using a Berlin Court-type Piezod 33 Meter,ZJ-4D,Institute of Measurements were performed at 25° C. using an Acoustic of Academia Sinica. Measurements of the dielectric constant and dielectric loss were performed at 1 kHz, 1 Vrms, and 25° C. using an LCR meter manufactured by Hioki Electronics Corporation. EXAMPLES

[0041] (Examples 1 to 10) Lead magnesium niobate-lead titanate (Pb(Mg 1 / 3 , Nb 2 / 3 )O 3 -PbTiO 3 )PbTiO 3 A single crystal

[0001] plate having a composition of 25 to 35 mol% and an outer dimension of 12×4 mm to 8×80 mm, polished and cut to a thickness of 0.2 mm to 0.5 mm is prepared. Then, chromium (Cr) is provided to a thickness of 20 nm on the upper and lower surfaces of the

[0001] plate (e.g., 15×4.0 mm) by a sputtering device. Gold is provided to a thickness of 200 nm on the chromium by a sputtering device to form electrodes. Next, the single crystal

[0001] plate provided with the electrodes is cut using a dicer blade to produce a piezoelectric vibrator.

[0042] FIG. 1 is a schematic diagram of the appearance of a piezoelectric vibrator, which is a piezoelectric single crystal vibrator with a length and width of 12 mm × width of 60 mm and a thickness of 0.3 mm. The phase transition temperature T rt is about 60°C to 100°C. The Curie temperature Tc is 110°C to 165°C. The coercive field Ec measured using a Sawyer Tower circuit was 2.0 to 3.5 kV / cm at room temperature. AC polarization and DC polarization were performed between the electrodes of this piezoelectric vibrator under the conditions shown in Table 1.

[0043] FIG. 2 shows a process diagram (a) of repeated AC polarization according to the present invention, and a process diagram (b) of conventional AC polarization performed only once. FIG. 3 is a schematic diagram showing AC polarization-depolarization-AC polarization according to the present invention. In FIG. 3, the vertical axis on the left side of the triangular waveform indicates temperature, and the horizontal axis indicates time change. Furthermore, in the ranges a, b, and c enclosed by squares in the triangular waveform, the waveform value is shown on the vertical axis on the right side corresponding to the voltage during AC polarization. In this embodiment, the number of repetitions is shown as 3, but it is the same for 2 to 5 times. The voltage, frequency, and number of cycles used here can be changed as appropriate according to the piezoelectric vibrator material, shape, and polarization temperature. FIG. 4 shows the frequency constant N in the thickness direction of a piezoelectric vibrator according to one embodiment of the present invention. t and the frequency constant in the longitudinal direction N 31 The ratio of N t / N 31 This shows the relationship between:

[0044] In this embodiment, 24 hours after the polarization treatment, the room temperature relative permittivity, dielectric loss DF (%), piezoelectric constant d33 (pC / N), resonance frequency (fr) and anti-resonance frequency (fa) in the thickness and length directions were measured, and the frequency constant N t and N 31 (and its ratio N t / N 31 ] were calculated respectively.

[0045] The following Tables 1 and 2 show various characteristics of piezoelectric vibrators polarized by applying an AC electric field, together with various characteristics of PMN-PT piezoelectric vibrators of the same shape to which an AC electric field is not applied. The values ​​in the tables are the average values ​​of four samples in each example. In Table 1, the length L and width W of the piezoelectric vibrator are 12 mm and 4 mm (L / W=3) for Examples 1-6, 60 mm x 12 mm (L / W=5) for Examples 7-8, and 60 mm x 7 mm (L / W=8.6) for Examples 9-10. All of the reference examples are 60 mm x 12 mm (L / W=5). All have a thickness of 0.3 mm.

[0046] [Table 1]

[0047] [Table 2]

[0048] As is clear from the results in Table 1, when AC polarization is performed under the conditions of the present invention, the frequency constant N, which is expressed as the product of the resonant frequency fr in the transverse vibration mode perpendicular to the polarization direction and the length L of the longest side in the vibration direction of the single crystal plate in the

[0100] direction, is 31 and the frequency constant N, which is expressed as the product of the resonance frequency fr of the longitudinal vibration mode parallel to the polarization direction and the thickness t of the single crystal plate in the vibration direction. t Ratio of N t / N 31 It was found that the frequency constant N 31 and the frequency constant in the thickness direction N t and the frequency constant N 31 The ratio of N t / N 31 The preferred range of N in the range indicated by α in FIG. t / N 31 The value of is preferably in the range indicated by β, and more preferably in the range indicated by β.

[0049] In the present invention, the frequency constant N t and N 31 Ratio of N t / N 31 The reason why the ratio of frequency constants N is set to 2.75 to 3.9 at 25°C, and more preferably 2.8 to 3.6, is that a piezoelectric vibrator having satisfactory electrical characteristics cannot be obtained if the ratio is below 2.75, and if the ratio is above 3.9, the phase transition temperature becomes 60°C or lower, and the temperature dependence of the piezoelectric characteristics becomes large. Therefore, from both of the above viewpoints, the ratio of frequency constants N t / N 31 is preferably 2.8 to 3.6 at 25° C., and more preferably 2.9 to 3.2.

[0050] As shown in Tables 1 and 2, the appropriate frequency constant ratio, N t / N 31 It is clear that the piezoelectric vibrators of Examples 1-10 having the above ranges exhibit superior electrical characteristics compared to vibrators outside these ranges. In addition, when the presence or absence of unwanted vibrations in the examples was confirmed, all were good without any problems. Furthermore, the dielectric breakdown of the piezoelectric vibrators of the examples was 5% or less, and a high manufacturing yield of 95% or more was obtained. However, half of the samples of Reference Example II (2 / 4) experienced dielectric breakdown, and the remaining two also showed large unwanted vibrations. As shown in Table 2, the value of the relative dielectric constant in the present invention is high, being 8000 or more and 15000 or less, and has the characteristic that electrical matching with the connection cable is easy, especially when a small rectangular vibrator is manufactured.

[0051] The present invention can be implemented in other forms than those described above without departing from the spirit of the present invention. The embodiments disclosed in this application are merely examples, and the present invention is not limited to these embodiments. The technical scope of the present invention is supported by the description of the specification of this application, is interpreted based on the description of the claims, and includes all modifications within the scope equivalent to the claims. [Explanation of symbols]

[0052] 1 Piezoelectric vibrator 2 electrodes E Electric field direction

Claims

1. A piezoelectric vibrator formed of a rectangular single crystal plate composed of a lead complex perovskite compound containing magnesium oxide, niobium oxide, and lead titanate, and having electrodes on both sides, the single crystal plate has a [001] crystal orientation plane as a main surface, a [100] plane and a [010] plane as side surfaces, and a ratio L / W of a length L of the single crystal plate in the [100] orientation to a width W of the single crystal plate in the [010] orientation is 3 to 8.6; The polarization state due to AC polarization and DC polarization is maintained, and a frequency constant N is expressed by the product of the resonance frequency fr in the transverse vibration mode perpendicular to the polarization direction and the length L. 31 and a frequency constant N expressed by the product of a resonance frequency fr in a longitudinal vibration mode parallel to the polarization direction and the thickness t of the single crystal plate. t Ratio of N t / N 31 is 2.77 to 3.86 at 25°C.

2. The ratio of the frequency constants N t / N 31 The piezoelectric vibrator of claim 1, wherein the modulus of elasticity is 2.8 to 3.6 at 25°C.

3. The lead complex perovskite compound is lead magnesium niobate (100-x)Pb(Mg 1/3 Nb 2/3 ) O 3 , lead titanate xPbTiO 3 The piezoelectric vibrator according to claim 1 or 2, which is a two-component system, has x mol % (x is a positive value) of lead titanate and (100-x) mol % of lead magnesium niobate, has a temperature Tm showing a maximum relative dielectric constant of 125°C to 150°C, and x = 27 or more and 32 or less.

4. The phase transition temperature T of the crystal structure of the lead complex perovskite compound rt The piezoelectric vibrator according to claim 3, wherein the temperature is 60° C. or higher and 110° C. or lower.

5. 5. A method for manufacturing a piezoelectric vibrator according to any one of claims 1 to 4, comprising the steps of: subjecting the single crystal plate, which has been initially AC polarized, to a heat treatment and AC polarization and depolarization at a temperature of 150°C or higher and 300°C or lower; and repeating the steps at least two to four times, after which the single crystal plate is subjected to a final AC polarization.

6. 6. The method for manufacturing a piezoelectric vibrator according to claim 5, wherein the AC electric field in the AC polarization is 1.0 kVrms / cm or more and 10 kVrms / cm or less (rms: Root Mean Square), and an AC electric field having a frequency of 0.01 Hz to 200 Hz using a triangular wave or a sine wave is applied for 4 to 200 cycles.

7. 7. The method for manufacturing a piezoelectric vibrator according to claim 5, wherein the temperature in the AC polarization is in the range of 40.degree. C. to 70.degree.

8. 8. The method for manufacturing a piezoelectric vibrator according to claim 5, wherein after the final AC polarization, a DC electric field in the range of 3.0 kV / cm to 5 kV / cm is applied between the front electrode and the back electrode of the single crystal plate for a period of 10 seconds to 1 minute.

9. 9. The method for manufacturing a piezoelectric vibrator according to claim 8, wherein the intensity of the DC electric field is 0.8 to 1.5 times the intensity of the AC electric field.

10. 10. The method for manufacturing a piezoelectric vibrator according to claim 9, wherein the AC electric field is 2.0 kVrms / cm or more and 4.0 kVrms / cm or less, the DC electric field is 3.0 kV / cm or more and 5.0 kV / cm or less, and the polarization temperature is in the range of 40°C to 70°C.

Citation Information

Patent Citations

  • Ultrasonic probe

    JP1995050898A

  • Piezoelectric ceramic composition, piezoelectric ceramic, piezoelectric element and oscillator

    JP2011068516A

  • Ultrasonic probe, piezoelectric vibrator, manufacturing method of ultrasonic probe, and manufacturing method of piezoelectric vibrator

    JP2014045411A

  • Piezoelectric vibrator, ultrasound probe, method for manufacturing piezoelectric vibrator, and method for manufacturing ultrasound probe

    JP2014187285A